Pengaruh NPM, DER dan TATO Terhadap Harga Saham Pada Subsektor Kosmetik dan Barang Keperluan Rummah Tangga - Puspayani; Riyanti (LPPM STIE EKA PRASETYA, 2025)
This study aims to analyze and empirically test the influence of several key financial indicators, namely Net Profit Margin (NPM), Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO), on stock prices in companies engaged in the cosmetics and household goods sub-sectors listed on the Indonesia Stock Exchange. The population in this study includes 7 companies, with 6 companies selected as samples using the purposive sampling method based on certain criteria, during the observation period from 2016 to 2023. This study uses secondary data obtained from the annual financial reports of each company as the main source of information. Data analysis was conducted through a quantitative approach by applying multiple linear regression methods, which were processed using SPSS statistical software version 27. The results of the analysis showed that simultaneously the four independent variables (NPM, CR, DER, and TATO) had a significant effect on the company's stock price. However, based on partial tests, only the Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) variables showed a significant effect on stock prices, while the Net Profit Margin (NPM) and Current Ratio (CR) variables did not provide a significant effect.